Performance modeling of an intelligent emergency evacuation system in buildings on accidental fire occurrence. (February 2019) - Sheeba, Angel A.; Jayaparvathy, R.
Highlights: To accommodate large influx of occupants many high rise buildings are constructed. Safety is uncertain in the time of an emergency due to events such as fire accidents. A generalized stochastic petri net model is developed for a multi floor building considering the two cases, with and without the human behavior constraints and evaluate the performances. The performance of the modeled system has been analyzed in terms of throughput, pre evacuation delay and evacuation time. This estimation can be used by the architects to design buildings with required stair-widths floor exits and other features such as to avoid congestion. With the inherent strong mathematical foundation of SPN based models compared to other modeling approaches, it is reliable to apply and analyze the behavior of occupants in high rise buildings. Abstract: Construction of multi-floor buildings have increased multifold in the urban areas due to scarcity of space for the growing population. There is a need for safe evacuation of people in such multi floor buildings during emergency situations such as fire occurrence. In this paper, we present an analytical model of the evacuation scenario on accidental fire using stochastic petri nets. The proposed evacuation model takes into account human behavior parameters such as panic among occupants, and realistic situations namely stampede in the stairwell, and distance of each occupant to the floor exits. The performance of the system is evaluated in terms of evacuation time, pre evacuation delay and average system throughput and compared with those of the evacuation model without human behavior and realistic constraints. The analytical results are validated using the real time evacuation drill measurements in a 10 storey building.